No rest for the women: Understanding the impact of on-call work for women in the emergency services. (3rd June 2018) - Jay, Sarah M; Paterson, Jessica L; Aisbett, Brad; Ferguson, Sally A
ABSTRACT: Background : The unpredictable, "on-call" component of the emergency services (ES) may be difficult to navigate in the context of domestic and work responsibilities, and especially difficult for women, given they tend to take on a greater household burden than do men. Our aim was to understand women's experiences in the ES, particularly the impact of being on-call and related coping strategies. Methods : Twenty-four women were recruited from two ES agencies in Australia. Participation involved a brief questionnaire and a 45–60-min interview. Interviews were recorded, and audio files were transcribed before analysis using nVIVO software. Results : Interview data identified two major themes: impact and management . Women talked about the impact of on-call for themselves (e.g. disturbed? sleep, fatigue and the relentlessness of the role) but also discussed the, largely negative, impact for their family/household. In terms of management, support (family, social and work) and planning and preparation were identified as important in helping women manage their multiple roles in the context of on-call unpredictability. Conclusion : The negative impacts of on-call work on women's sleep supports existing quantitative and qualitative data in the broader on-call area. For those women with children, managing their care presents one of the biggest challenges to being able to manage the on-call component of their work. Future research should to focus on quantifying the impact of on-call for both men and women, particularly the "relentlessness" of the work identified in this study and whether this toll changes based on other factors such as experience, role or gender.